Odpowiedź :
x - cena książki
x + 150 - cena maskotki
x + x + 150 - cała suma pieniędzy
x+150 = [tex]\frac{3}{4}[/tex] (2x+150)
x+150 = [tex]\frac{6}{4}[/tex]x + [tex]\frac{450}{4}[/tex]
[tex]\frac{4}{4}[/tex]x - [tex]\frac{6}{4}[/tex]x = [tex]\frac{450}{4}[/tex] - [tex]\frac{600}{4}[/tex]
- [tex]\frac{2}{4}[/tex]x = - [tex]\frac{150}{4}[/tex] / ·(-[tex]\frac{4}{2}[/tex])
x = 75
cała suma pieniędzy: 75 + 75 + 150 = 300 zł
Odpowiedź:
x - suma pieniędzy
[tex]\frac{3}{4}[/tex]x - cena maskotki
[tex]\frac{1}{4}[/tex]x - cena książki
[tex]\frac{3}{4}[/tex]x - 150 = [tex]\frac{1}{4}[/tex]x / [tex]-\frac{3}{4}x[/tex]
- 150 = [tex]-\frac{2}{4}[/tex]x / :(-1)
150 = [tex]\frac{2}{4}x[/tex] / *2
x = 300
Sprawdzenie:
225 - 150 = 75
Odp.: Dziewczynka miała 300 zł.